Point-based TLD dosimetry during CT-guided cervical vertebral biopsy: Absorbed dose, scatter radiation, and protection optimization - Kesmezacar, Fahrettin Fatih; Mahmutoglu, Abdullah Soydan; Ozgur, Eren; Tunay, Abdurrahman; Kayaokay, Duygu Tuncman; Gunay, Osman; Karacam, Songul Cavdar; Oksuz, Didem Colpan; Demir, Mustafa; ALMisned, Ghada; Tekin, H. O. (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
This study aimed to experimentally quantify point-based absorbed radiation doses at predefined anatomical locations during computed tomography (CT)-guided cervical vertebral bone biopsy using an anthropomorphic phantom and calibrated thermoluminescent dosimeters. A CT-guided cervical biopsy procedure was simulated on an Alderson Rando (R) anthropomorphic phantom using a posterolateral approach. Absorbed dose measurements were performed using MTS-100 LiF:Mg,Ti thermoluminescent dosimeters placed at predefined surface and internal anatomical locations corresponding to radiosensitive organs, including the thyroid gland, salivary glands, ocular lens region, pituitary projection, and posterior cervical vertebra. Dosimeters were calibrated under standard diagnostic X-ray beam quality, and measurement uncertainty was evaluated using Type A and Type B components. Scanning was performed using clinically representative low-dose CT acquisition settings, while scanner-reported CTDIvol and DLP values were used only to describe the imaging protocol and not for organ-dose estimation. The highest point-based absorbed dose was measured at the posterior cervical vertebra location, with a value of 9.15 mGy. Measurement points corresponding to adjacent glandular structures showed comparable absorbed doses, including 8.95 mGy at the right submandibular gland and 8.84 mGy at the right parotid gland. Thyroid surface doses of 8.22-8.26 mGy were approximately 28% higher than deep thyroid lobe doses of 6.34-6.49 mGy. Cranial locations outside the primary beam path also received measurable scatter radiation, with corneal and pituitary projection doses of approximately 5.3-5.5 mGy. These findings demonstrate that CT-guided cervical vertebral biopsy produces localized absorbed dose not only at the target region but also at nearby and distant radiosensitive anatomical points through scatter and helical acquisition geometry. It can be concluded that TLD-based point-dose data provide a radiation physics framework for CT dose optimization, uncertainty-aware dosimetry, and protection strategies in interventional CT procedures.
Keywords: CT-guided biopsy; Cervical vertebra; Radiation dosimetry; Thermoluminescent dosimeters; Anthropomorphic phantom; Patient safety; EXPOSURE; LENS; EYE; Chemistry; Nuclear Science & Technology; Physics